Telegraph from the Assembly of the Captive European Nations to the President of the UN Special Committee on Hungary - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Assembly of Captive European Nations Expresses sincere admiration for the thoroughness and objectivity of the report of the Special Committee on Hungary.